2021
DOI: 10.51967/tanesa.v22i1.478
|View full text |Cite
|
Sign up to set email alerts
|

Dampak Pertambangan Batubara Terhadap Sosial dan Ekonomi Masyarakat di RT. 17, Desa Loa Duri Ulu, Kecamatan Loa Janan, Kabupaten Kutai Kartanegara

Abstract: Penelitian ini dilatarbelakangi oleh banyaknya kegiatan pertambangan batubara yang ada di di Kabupaten Kutai Kartanegara yang berdampak langsung terhadap kehidupan sosial dan ekonomi masyarakat. Kegiatan pertambangan batubara tersebut tentu akan mengakibatkan dampak positif dan negatif, baik terhadap lingkungan, maupun ke masyarakat sekitar yang bersifat ekonomis dan sosial. Salah satu penyebabnya yaitu terjadinya proses konflik sosial atau perubahan tatanan kehidupan dalam bermasyarakat, dimana terjadi pola p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…According to Nggeboe (2004, p. 46), coal mining risks triggering social conflict if the land acquisition process is detrimental to the community. According to Azwari and Rajab (2021), coal mining often results in social conflict because local communities feel they are not involved in the process before and during mining, both as workers and as recipients of corporate social responsibility (CSR) programs. The research findings of Subarudi et al (2016) regarding coal mining conflict resolution found that one of the root causes of social conflict is poor licensing management, so the community suffers losses.…”
Section: Potential Conflict and Social Tension In Mining Areasmentioning
confidence: 99%
“…According to Nggeboe (2004, p. 46), coal mining risks triggering social conflict if the land acquisition process is detrimental to the community. According to Azwari and Rajab (2021), coal mining often results in social conflict because local communities feel they are not involved in the process before and during mining, both as workers and as recipients of corporate social responsibility (CSR) programs. The research findings of Subarudi et al (2016) regarding coal mining conflict resolution found that one of the root causes of social conflict is poor licensing management, so the community suffers losses.…”
Section: Potential Conflict and Social Tension In Mining Areasmentioning
confidence: 99%
“…Kekayaan yang dihasilkan diharapkan dapat meningkatkan nilai kapasitas masyarakat untuk menghadapi masa depan mereka sendiri. Kombinasi aspek sosial, ekonomi, dan lingkungan harus diperhitungkan selama proses pemindahan untuk mengidentifikasi dampak apa pun sesegera mungkin (Azwari & Rajab, 2021). Bentuk dampak yang terlihat dari adanya aktivitas industri pertambangan nikel adalah kebutuhan lahan semakin bertambah dengan masuknya migrasi untuk memenuhi kebutuhan ekonomi dan menjadi tenaga kerja.…”
Section: Pendahuluanunclassified
“…This assumption has turned one hundred degrees from the reality that occurs on earth that mining has caused many social and environmental problems (horizontal and vertical social conflicts, agrarian conflicts, and environmental damage). Mining business practices have not provided much welfare for the community (Azwari & Rajab, 2021;Asnawi, 2019;Jimmy & Merang, 2020).…”
Section: Forms Of Social Conflict (Block Access To the Sape-bajo-east...mentioning
confidence: 99%